Bilateral Lower Limb Disabling Claudication in a Young Man: A Case of Mönckeberg’s Arteriosclerosis - Khalid Abdelaziz Mowafy (Vascular and Endovascular Review, 2019)
Mönckeberg’s arteriosclerosis, also called medial calcific sclerosis or Mönckeberg’s sclerosis, is a form of vessel hardening due to increased calcium deposits in the tunica media layer. There is disagreement over its clinical significance and aetiology and its relation to atherosclerosis and vascular calcification. Its clinical presentations and treatment are still debated. More effort should be directed on attempting to distinguish between atherosclerotic lesions and Mönckeberg’s lesions on the basis of age, location and the pattern of calcifications where there is considerable overlap between intimal or medial and involvement of the internal elastic lamina border between those planes. In-depth research is still needed to create consensus guidelines for the diagnosis and management of this condition. This article includes a review of the literature and a case report of a 22-year-old man with the condition.